Pengaruh Kedatangan Wisatawan Asing, KUK, dan Nilai Produksi UMK dan UMKM terhadap Angka Pengangguran Di Provinsi Bali - Warmadewi, Anak Agung Sagung Putri; Natha, I Ketut Suardhika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 9, September 2016 (pp. 902 - 1010), 2016)
The high unemployment rate in our country is because too many of the labor force annually. Small and medium enterprises also proved capable of providing solutions to overcome the problem of unemployment in Indonesia. The study aims to analyze the influence of the number of foreign tourist arrivals, small business loans (KUK) in trade, hotels and restaurants, and the production value of SMEs on the unemployment rate in the province of Bali in the period 1993-2013. Studies conducted in the province of Bali, using the library (library research). The data used in this research is time series data on the value of the number of foreign tourists, Small Business Credit (KUK), the production value of Micro, Small and Medium Enterprises as well as the unemployment rate in the province of Bali which is obtained from the Central Bureau of Statistics (BPS), as well as the Planning Board and (Bappeda) of Bali from the year 1993 to 2013 with the technique of multiple linear regression analysis. The results of the analysis to prove the number of foreign tourist arrivals, Small Business Credit (KUK) on the Trade, Hotel and Restaurant, and the production value of SMEs simultaneous positive effect on the unemployment rate in the province of Bali in the period 1993-2013. The number of foreign tourist arrivals, Small Business Credit (KUK) on the Trade, Hotel and Restaurant, and the production value of SMEs partially negative effect on the unemployment rate in the province of Bali in the period 1993-2013. Small Business Credit (KUK) on the Trade, Hotel and Restaurant dominant influence on the unemployment rate in the province of Bali in the period 1993-2013.
Keywords: foreign tourist arrivals, (KUK), SMEs and the unemployment rate in the province of Bali